Stenotrophomonas goyi sp. nov., a novel bacterium associated with the alga Chlamydomonas reinhardtii [version 3; peer review: 2 approved] - María Jesus Torres; David González-Ballester; Neda Fakhimi; Alexandra Dubini (F1000Research, 2023)
Background A culture of the green algae Chlamydomonas reinhardtii was accidentally contaminated with three different bacteria in our laboratory facilities. This contaminated alga culture showed increased algal biohydrogen production. These three bacteria were independently isolated. Methods The chromosomic DNA of one of the isolated bacteria was extracted and sequenced using PacBio technology. Tentative genome annotation (RAST server) and phylogenetic trees analysis (TYGS server) were conducted. Diverse growth tests were assayed for the bacterium and for the alga-bacterium consortium. Results Phylogenetic analysis indicates that the bacterium is a novel member of the Stenotrophomonas genus that has been termed in this work as S. goyi sp. nov. A fully sequenced genome (4,487,389 base pairs) and its tentative annotation (4,147 genes) are provided. The genome information suggests that S. goyi sp. nov. is unable to use sulfate and nitrate as sulfur and nitrogen sources, respectively. Growth tests have confirmed the dependence on the sulfur-containing amino acids methionine and cysteine. S. goyi sp. nov. and Chlamydomonas reinhardtii can establish a mutualistic relationship when cocultured together. Conclusions S. goyi sp. nov. could be of interest for the design of biotechnological approaches based on the use of artificial microalgae-bacteria multispecies consortia that take advantage of the complementary metabolic capacities of their different microorganisms.